PENGEMBANGAN KECAKAPAN HIDUP SISWA TUNANETRA MELALUI KOLABORASI KONSELOR DAN GURU DI SMA TERPADU : Pendekatan Konseling Dalam Pembelajaran Tunanetra Pada Beberapa SMA Di Bandung - Mega Iswari, - (2005)
DEVELOPMENT OF SKILLS OF VISUALLY IMPAIRED STUDENTS THROUGH COLLABORATION OF CONSELOR AND TEACHER This study began with problems and needs of life skills of visually impaired student in Integrated High School in order to enable them to be independent and to achieve happiness in life later. In this case counselling services has strategic roles to facilitate visually impaired student in coping with problems as well as developing their potentials. The purposes of this study is to find principles of counselling to develop life skills of visually impaired student in integrated high schools in Bandung City in these following high schools : SMA Negeri 6, SMAN 7, SMA Puragabaya and SMA PGJI. Method of study used is descriptive method with qualitative approach that links with problems of the visually impaired students. Thereafter, the study is designed with Research and Development (RD) approach to develop life skills needed by visually impaired students through collaborations of counsellors and teacher in integrated schools by procedure of: (1) revealing objectives conditions of the problems and needs of visually impaired students in high schools. (2) carrying data analysis in the field. (3) formulating counselling models to develop life skills of visually impaired students based on field analysis and theoretical studies. (4) conducting feasibility examination, revising and formulating principles and models of counselling through seminars and workshops with the teachers and counsellors, and (5) perfecting principles and models. That data is processed qualitatively. From the study, it is found that the principles of life skills for visually impaired students, consist of (1) optimizing senses other than sight, (2) stressing understanding that impairment is not the end of everything, (3) understanding the mind of visually impaired students, (4) cultivating self confidence, (5) making collaborations in doing counselling guidance an essence of program implementation, (6) using a multidisciplinary approach, (7) cooperating with people who work with the visually impaired students, (8) through counselling improving self-confidence in visually impaired students, (9) preparing training and practice in accordance with level of the impairement, (10) the counsellor not only providing information, but students are brought to real situations. These principles of counselling can help visually impaired students in developing. 1) personal life skills, that is to become self-confidence, trust other people, not anxious and hesitating, 2) social life skills, that is to become more sociable, to fee! safer, and open to socialize, able to interact, and communicate well, 3) academic skills, that it to acquire group-learning skills, get a good studying habits, and 4) vocational skills, that is able to plan to study further to higher education, and choose a profession that fits their interest and talents. Based on above finding, it is recommended that the principles and models of life skills counselling for the visually impaired students ca be applied by counsellor and teacher in integrated high schools.